2010
DOI: 10.1111/j.1365-2958.2010.07464.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for the essential YycG sensor histidine kinase in sensing cell division

Abstract: Summary The YycG (WalK) sensor histidine kinase coordinates cell wall remodeling with cell division in Gram-positive bacteria by controlling the transcription of genes for autolysins and their inhibitors. Bacillus subtilis YycG senses cell division and is enzymatically activated by associating with the divisome at the division septum. Here it is shown that the cytoplasmic PAS domain of this multi-domain trans-membrane kinase is a determining factor translocating the kinase to the division septum. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 50 publications
1
66
3
Order By: Relevance
“…1) proposes that the WalRK TCS senses cell growth through septal location of WalK and is activated by a signal emanating from the divisome (Fukushima et al, 2008(Fukushima et al, , 2011. WalR-P activates expression of autolysins (CwlO, YocH and LytE), cell-wall-associated (YdjM) and cell division (FtsZ) proteins while repressing autolysin-modulating (YjeA) and -inhibiting (IseA) activities thereby promoting cell wall synthesis during cell elongation (Bisicchia et al, 2007;Fukushima et al, 2008Fukushima et al, , 2011. During phosphate limitation, the WalK signal is lowered or absent due to reduced growth rate, but peptidoglycan synthesis is still required (Bisicchia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…1) proposes that the WalRK TCS senses cell growth through septal location of WalK and is activated by a signal emanating from the divisome (Fukushima et al, 2008(Fukushima et al, , 2011. WalR-P activates expression of autolysins (CwlO, YocH and LytE), cell-wall-associated (YdjM) and cell division (FtsZ) proteins while repressing autolysin-modulating (YjeA) and -inhibiting (IseA) activities thereby promoting cell wall synthesis during cell elongation (Bisicchia et al, 2007;Fukushima et al, 2008Fukushima et al, , 2011. During phosphate limitation, the WalK signal is lowered or absent due to reduced growth rate, but peptidoglycan synthesis is still required (Bisicchia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…YycG kinase, like MtrB, associates with the septa, and its septal association is essential for its activation and for controlling the expression of several genes involved in cell wall metabolism and turnover (34,35). Pertinent to this study is the observation that the YycG kinase interacts with PbpB (FtsI) and with other proteins, such as FtsL and DivIB (34). These studies also showed that the septal localization of YycG is not affected by the depletion of DivIB and FtsL and that studies with PbpB depletion are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…What domain of YycG kinase was interacting with the septum? Tetsuya was able to show that the cytoplasmic PAS domain of this multiple-domain transmembrane kinase was a determining factor translocating the kinase to the division septum (19).…”
Section: An Essential Two-component System Connecting Cell Wall Growtmentioning
confidence: 99%